RANTAI PASOK KAKAO DI KECAMATAN TANGSE KABUPATEN PIDIE - zakiah zakiah; Qhisthina Atikah (Jurnal Bisnis Tani, 2023)
This study aims to analyze marketing channels, marketing margins and cocoa marketing efficiency in Tangse District, Pidie District, this research was conducted in January 2022 in Tangse District, Pidie District. The sampling technique used was the Snowball Sampling technique. The types of data in this study are primary and secondary. The analytical method used in this research is descriptive and quantitative analysis methods. The results showed (1) the cocoa marketing channel consisted of two types, namely channel I from farmers, village traders then after that to sub-district traders then exported to the processing industry and channel II, namely from farmers to village traders, collectors and sub-district traders then exported. to the processing industry (2) in channel I produce a marketing margin of Rp. 8,000/kg while channel II produces a margin of Rp. 8,400/kg, Farmer's share in channel I is 76.05% and channel II is 75.65%, this shows the largest share received by farmers is channel I but in the research area the most widely used channel is channel II (3) marketing efficiency of channel I is 4.22% while channel II is 5.21%, both types of channels are efficient because both types include efficiency criteria between 0-33%, but in the research location the most widely used is type II, when viewed from the farmer share and p efficiency. The marketing is better for type I, this is because in type II the most benefit is the collector traders while type II is the village trader.